Muamalah Kontemporer dan Fatwa Ulama: Dinamika dan Implementasi di Indonesia - Hanafi Yunus (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to examine the dynamics of fatwas issued by Islamic scholars in addressing contemporary Muamalah issues in Indonesia and to identify the roles, challenges, and potential alignment between fatwas and positive legal regulations. Fatwas issued by scholars play a crucial role in providing legal guidance for Muslims in Indonesia, particularly in the context of technological and modern economic developments such as e-commerce, sharia fintech, and digital investments. Using a qualitative approach with literature study, this research analyzes various fatwas issued by the Indonesian Ulema Council (MUI) and the factors influencing the scholars' decisions, including technological advancements, societal needs, and globalization. Furthermore, this study identifies obstacles in the implementation of fatwas, such as limited public understanding and potential conflicts with government regulations. The research finds that, despite the challenges, there is significant potential for aligning fatwas with positive legal regulations in Indonesia. Collaboration between scholars, religious institutions, and the government is essential to ensure the effective implementation of fatwas and create an inclusive and just legal system for Muslims. The synergy between fatwas and regulations is expected to support the sustainable development of the Islamic economy and contribute to the building of a more prosperous and harmonious Indonesian society.